Possibility of a case of pneumonia caused by green tea contaminated with Pseudomonas aeruginosa and countermeasures against it. (4th July 2022) - Oie, Shigeharu; Kawai, Shinya
Abstract: We report a patient who developed pneumonia after prolonged use of spray bottle containing green tea for hydration purposes. The cause was suspected to be a contamination of green tea because the patient's symptoms persisted and did not improve until stopping the use of the spray bottle and we also found the green tea in the spray bottle to harbor a high number of Pseudomonas aeruginosa (1.2 × 10 7 colony forming units (cfu)/mL). It is not uncommon to use green tea for hydration or gargling purposes in some patient care settings considering the antibacterial effects of catechins contained in green tea. Our findings suggest the importance of keeping vigilance on consuming green tea in spray bottles in hospital settings since it may readily be contaminated by pathogens such as P. aeruginosa . HIGHLIGHTS: A cause of nosocomial pneumonia was determined to be caused by the use of spray bottle containing green tea for hydration purposes. Spray bottle containing green tea was determined to harbor high number of Pseudomonas aeruginosa, a common nosocomial pathogen. Microorganisms such as P. aeruginosa were determined to grow well in manufactured green tea products, but not in black tea or coffee products.